Locating and applying critical discourse analysis within education policy - Lester, Jessica Nina; Lochmiller, Chad R.; Gabriel, Rachael (Education Policy Analysis Archives, 2016)
This article introduces the first of a two-part Special Issue on Discourse Perspectives and Education Policy. This first special issue is focused on critical discourse analysis and education policy. Within this article, we provide a brief overview of discourse analysis generally and critical discourse analysis specifically. We highlight some of the ways in which policy researchers have applied the theories and methods associated with CDA and note the methodological and substantive contributions of this work. Then, we provide an overview of the six papers included within this special issue, noting each paper’s key points and explicit links to policy. We conclude by pointing to future directions for research at the intersection of education policy and discourse studies.